Validity of time-dependent trial states for the Holstein Polaron - Luo, Bin (2010)
Validity of three time-dependent trial states for the Holstein Hamiltonian, namely, the D2, Merrifield and D Ansatze has been examined in detail with regards to their deviations from the exact solution to the time-dependent Schrodinger equation. Linear absorption spectra are also calculated as an additional indicator of the Ansatz validity. It is found that the D Ansatz is the most accurate trial state of the three, and all Ansatze fail to provide an adequate description of system dynamics in the weak-coupling regime.